Fungsi, Peran, dan Kategori Sintaksis Bahasa Indonesia dalam kalimat Berita dan Kalimat Seruan pada Naskah Pidato Bung Karno 17 Agustus 1945 - Armita Enggarwati; Asep Purwo Yudi Utomo (Institut Agama Islam Negeri Curup, 2021)
The manuscript of Bung Karno's speech on August 17, 1945 is an example of the use of Indonesian in official documents and state speeches so that the sentences in them are good to analyze. There are many syntactic symptoms found in it that are interesting to study, including the structure of descriptive sentences and imperative sentences which can be analyzed based on the functions, roles, and syntactic categories of Indonesian. This research consists of two problems, namely (1) regarding the functions, roles, and syntactic categories of news sentences in Bung Karno's speech on August 17, 1945, (2) regarding the functions, roles, and syntactic categories of exclamatory sentences in Bung Karno's speeches on August 17, 1945. This study aims to describe the types of functions, roles, and syntactic categories of news sentences and exclamations of Bung Karno's speech on August 17, 1945. The research method used is descriptive qualitative research method. Data collection was carried out using the note-taking technique and data analysis using content analysis techniques. The results of this study found that syntactic functions include subject, predicate, object, description, and complement; the roles that are found are as actors, tools, and experiences occupying the function of the subject; and categories include pronouns, nouns, transitive verbs, intransitive verbs, adverbial phrases, verbal phrases, nominal phrases, prepositional phrases, adjective phrases, and numeral phrases. From this research, it can be seen that one sentence can contain more than one type of function, role, and syntactic category. This research is expected to show the functions, roles, and syntactic categories in declarative and imperative sentences in Bung Karno's speech on August 17, 1945, which is the speech of the proclamation of Indonesian independence.